The Diverse Roles of FLOWERING LOCUS C in Annual and Perennial Brassicaceae Species - Soppe, Wim J. J.; Viñegra de la Torre, Natanael; Albani, Maria C. (Frontiers in Plant Science, 2021)
Most temperate species require prolonged exposure to winter chilling temperatures to flower in the spring. In the Brassicaceae, the MADS box transcription factor FLOWERING LOCUS C (FLC) is a major regulator of flowering in response to prolonged cold exposure, a process called vernalization. Winter annual Arabidopsis thaliana accessions initiate flowering in the spring due to the stable silencing of FLC by vernalization. The role of FLC has also been explored in perennials within the Brassicaceae family, such as Arabis alpina. The flowering pattern in A. alpina differs from the one in A. thaliana. A. alpina plants initiate flower buds during vernalization but only flower after subsequent exposure to growth-promoting conditions. Here we discuss the role of FLC in annual and perennial Brassicaceae species. We show that, besides its conserved role in flowering, FLC has acquired additional functions that contribute to vegetative and seed traits. PERPETUAL FLOWERING 1 (PEP1), the A. alpina FLC ortholog, contributes to the perennial growth habit. We discuss that PEP1 directly and indirectly, regulates traits such as the duration of the flowering episode, polycarpic growth habit and shoot architecture. We suggest that these additional roles of PEP1 are facilitated by 1) the ability of A. alpina plants to form flower buds during long-term cold exposure, 2) age-related differences between meristems, which enable that not all meristems initiate flowering during cold exposure and 3) differences between meristems in stable silencing of PEP1 after long-term cold, which ensure that PEP1 expression levels will remain low after vernalization only in meristems that commit to flowering during cold exposure. These features result in spatiotemporal seasonal changes of PEP1 expression during the A. alpina life cycle that contribute to the perennial growth habit. FLC and PEP1 have also been shown to influence the timing of another developmental transition in the plant, seed germination, by influencing seed dormancy and longevity. This suggests that during evolution, FLC and its orthologs adopted both similar and divergent roles to regulate life history traits. Spatiotemporal changes of FLC transcript accumulation drive developmental decisions and contribute to life history evolution.